Desenvolvendo e gerenciando compostagem de resíduos sólidos urbanos: para geração de renda e repasse de tecnologia à acrevi - Sousa Júnior, Francisco Souto de (2011)
Nowadays, as well as in the past decades, the dumping of biodegradable organic waste in landfill is common practice in Brazil, as well as in most parts of the world. Nevertheless due to its rapid decomposition and release of odors, this practice hamper’s the operation and implementation of a recycling system. These facts encouraged our research to find an efficient system for the management of organic waste, not only for the use of official workers responsible for managing these wastes, but also for non-governmental institutions. The Recycling for Life Community Association – ACREVI (Associação Comunitária Reciclando para a Vida), together with the municipal authorities of Mossoró-RN, Brazil, have assumed the social role of collecting and recycling solid waste produced by most of the local population. However, it was observed that the organic waste it collected was not receiving any treatment. This present work aims to make compost with mixed waste (green waste and organic household), and then do chemical analysis of the material in view to use the waste as organic fertilizer. The objective being: to share the knowledge acquired by putting it into a very simple language accessible to people with little education. The experiment was conducted at ACREVI, Mossoró (RN), and the compost was obtained following the method "windrow", forming three cells (I, II, III) with conical shape, dimensions of 1.6 meters and 2.0 meters in diameter for cells I and II, and 1.0 meters high and 2.0 meters in diameter for cell III. The process was accompanied by analysis: CHN elemental, a variation of cell temperature, humidity, pH, TKN, bulk density, nutrients and heavy metals. Stabilized organic compounds reached the C/N ratio of 10.4/1 cell I and 10.4/1 in the cell II in the cell, showing how good soil conditions, with potential to improve the physical properties of any soil and pH acid soils, has presented the cell III at the end of the process the C/N 26/1, is a high ratio may be associated with the stack size III, thus changing the optimal conditions for the occurrence of the process. The levels of heavy metals in the analyzed compounds were lower than those established by the SDA normative instruction, Nº 27, of 5 June, 2006. The use of pruning trees and grass are used in small-scale composting, while generating a quality compost in the final process, it also created an important condition for a correct sizing of the composting piles. Under the studied conditions it is not advisable to use cells with a height of 1.00 m in height and 2.00 m in diameter, as these do not prevent the rapid dissipation of heat and thus can not be a good product at the end of composting. The composting process in the shed of the association and the preparation of the primer enabled the development of an alternative technology to generate income for members of ACREVI.